PENGARUH PERKEMBANGAN INDUSTRI MANUFAKTUR (SUBSEKTOR PENGGALIAN) TERHADAP PENDAPATAN â€œPAJAK PENGAMBILAN BAHAN GALIAN GOLONGAN Câ€ DI KABUPATEN TUBAN - KARMIRATIN, LAILATUL (Jurnal Akuntansi AKUNESA, 2012)
The purpose of this study was to describe the development of the manufacturing (sub-excavation) related to the exploitation of minerals group C with mineral tax revenue collection group C in 2007-2011, and the factors that influence decision-mineral tax revenue group C in Tuban. This study is a descriptive study with qualitative approach and uses primary data and interviews conducted in the office of Dinas Pendapatan, Pengelolaan Keuangan dan Aset Daerah (DPPAKD) and Dinas Pertambangan dan Energi Kabupaten Tuban. It can be concluded that the manufacturing (sub-excavation) in Tuban has developed over the past five years, from 2007 to 2011 seen from the increasing number of exploitation of raw materials production. Development of the mineral collection of tax revenue group C in Tuban on average each year has increased, from 2007 to 2011. Factors that influence the increase in tax revenue collection of minerals group C is an increasing number of mineral exploitation and changes the central government regulations or local government. Another factor that affects the tax revenue loss is the presence of illegal miners who took part in the exploitation of minerals in group C. Keywords: exploitation mineral group C, mining tax group C, government regulations, illegal miners